Sexual violence against children and adolescents: the profile of the victim and the aggressor in the crime of rape of the vulnerable (Research, Society and Development, 2020)
This article aims to present the profile of the victim and the aggressor in the crime of rape of the vulnerable, in the state of Pará, in the years 2017 and 2018. The study involved the analysis of the data provided by the Secretariat of Intelligence and Criminal Analysis (SIAC ), linked to the Pará Public Security Secretariat (SEGUP). It is a study with a quantitative approach, exploratory and descriptive. By analyzing the data, it was found that the crime of rape of the vulnerable stands out among the other crimes committed against children and adolescents, with a total of 2,298 cases recorded in 2017 and 2,963 cases of other crimes, as well as 2,475 cases registered in 2018 and 3,203 cases of other crimes. Regarding the profile of the aggressor, it was possible to identify that 99.05% of the aggressors are male and 0.95% are female. In the case of victims, the opposite occurs, with 87.88% of the victims being female and 12.12% male, and among them, 56.17% are children and 43.83% are adolescents, in years 2017 and 2018. In order to identify the existence of significant differences between the number of crimes per year, a statistical analysis was applied, making it possible to verify that there was no significant difference between the amount of crime per article and the average amount of crime per year, as well as there was no difference. between the amount of crime per city and the average amount of crime per year.